Sagot :
Answer:
1. p = { 3, -3)
2. n= { 2, 6}
Step-by-step explanation:
1. 6/p - 2p/3 = 0
multiply both sides by 3p
(6/p - 2p/3 = 0) x 3p
(6/p)(3p) - (2p/3)(3p) = (0)(3p)
(6)(3) - (2p)(p) = 0
18 - 2p^2 = 0
2p^2 = 18
divide both sides by 2
(2p^2)/2 = 18/2
p^2 = 9
√p^2 = √9
p = +/- 3
2. 8/n+2 + n-2/4 = 2
multiply both sides by 4(n+2)
(8/n+2 + n-2/4 = 2) x 4(n + 2)
(8)(4) + (n-2)(n+2) = 2x4(n+2)
32 + n^2 - 4 = 8(n+2)
32 + n^2 - 4 = 8n + 16
n^2 - 8n + 32 - 4 - 16 = 0
n^2 - 8n + 12 = 0
(n-6)(n - 2) = 0
n-6 = 0
n=6
n-2 = 0
n= 2